The indirect effects of servant leadership behavior on organizational citizenship behavior and job performance - TURHAN, GÜLDEN (My University, 2013)
The relationship between leader and followers plays a vital role, particularly in educational institutions where a keen understanding of human character and high level of social interaction ought to be facilitated. For this reason, in stark contrast to contemporary leaders who see people only as units of production or expendable resources in a profit and loss statement, servant leadership focuses on meeting the needs of followers, making them reach their maximum potential and so perform optimally in order to achieveorganizational goals and objectives. This study examines the effects of servant leadership behaviors of private college principals on teachers’ organizational citizenship behavior and job performance. Using 300 respondents from the private education institutes in Turkey, servant leadership behavior is examined for its indirect effects on organizational citizenship behavior and job performance by its impact on organizational justice. Organizational justice acts as a mediator between the variables in question. All the resultsare in support of the studied mediation effects. Implications of the findings and suggestions for future research are discussed.
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim ve Organizasyon; Social Sciences and Humanities; Management; Management and Organization; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Genel Karar Bilimleri; Karar Bilimleri (çeşitli); Strateji ve Yönetim; Genel İşletme, Yönetim ve Muhasebe; İşletme ve Uluslararası Yönetim; Pazarlama; Sosyal Bilimler ve Beşeri Bilimler; General Decision Sciences; Decision Sciences (miscellaneous); Strategy and Management; General Business, Management and Accounting; Business and International Management; Marketing; Social Sciences & Humanities; Servant leadership behavior; Organizational citizenship behavior; Job performance; Organizational justice